PEMILIHAN LAGU PADA PEMBELAJARAN VOKAL ANAK-ANAK: DI SANGGAR MUSIK AMABILE - Ariswanto, Elthon Oktavian; Irawan, Ricky; Laksmi, Desak Made Suarti (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2024)
The activity program MBKM or Independent Campus Learning guides students in implementing a learning process according to their deepened interest and knowledge through observation or field practice in the Teaching Assistance program. In the Teaching Assistance program, a specific music learning takes place, particularly vocal instruments or singing. Vocal learning is conducted at the Amabile Music Studio, which focuses or selecting song materials for children. The objective of this learning is to understand the process of selecting song materials for children, how techniques or applied to the learned song materials, and what challenges arise in the process of selecting song materials. The inclusion of this topic in writing is intended to inform the wider community about the process of implementing vocal learning, especially in preparing learning materials. The methods used in this writing are observation, assessment, and interviews with informants. The results of this learning include the process of preparing teaching materials, the development and application of students singing techniques, and the learning process from the song materials provided by the instructor.